Symptomatic or asymptomatic SAR-CoV-2 positive divers should be medically evaluated before returning to scuba diving - Morin, Jean; Vallée, Nicolas; Dufresne, Pierre-Louis; Rives, Sarah; Lehot, Henri; Daubresse, Lucille; Roffi, Romain; Druelle, Arnaud; Cungi, Pierre-Julien; Blatteau, Jean-Eric (Frontiers in Physiology, 2022)
Introduction: In order to allow the resumption of diving activities after a COVID-19 infection, French military divers are required to undergo a medical fitness to dive (FTD) assessment. We present here the results of this medical evaluation performed one month after the infection. Methods: We retrospectively analyzed between April 2020 and February 2021 200 records of divers suspected of COVID-19 contamination. Data collected included physical examination, ECG, blood biology, chest CT scan and spirometry. Results: 145 PCR-positive subjects were included, representing 8.5% of the total population of French military divers. Two divers were hospitalized, one for pericarditis and the other for non-hypoxemic pneumonia. For the other 143 divers, physical examination, electrocardiogram and blood biology showed no abnormalities. However 5 divers (3.4%) had persistent subjective symptoms including fatigability, exertional dyspnea, dysesthesias and anosmia. 41 subjects (29%) had significant decreases in forced expiratory flows at 25-75% and 50% on spirometry (n=20) or bilateral ground-glass opacities on chest CT scan (n=24). Only 3 subjects were affected on both spirometry and chest CT. 45% of these abnormalities were found in subjects who were initially asymptomatic or had non-respiratory symptoms. In case of abnormalities, normalization was obtained within 3 months. The median time to return to diving was 45 days. Conclusion: Our study confirms the need for standardized follow-up in all divers after COVID-19 infection and for maintaining a rest period before resuming diving activities.